2018
DOI: 10.15288/jsad.2018.79.826
|View full text |Cite
|
Sign up to set email alerts
|

Is Restricting Sales of Malt Liquor Beverages Effective in Reducing Crime in Urban Areas?

Abstract: We evaluated the effects of outlet and small area level malt liquor policies on crime in 10 U.S. cities and hypothesized that more restrictive malt liquor policies would be associated with greater reductions in crime. Method: We used a pooled time-series study design (i.e., panel regression) with comparison areas to test our hypothesis. Quarterly crime rates in targeted areas were compared 3 years before and after policy adoption. Four crime outcomes were analyzed: Selected Part II crimes, assaults, vandalism/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
4
2
Order By: Relevance
“…Our findings suggest that AIAs may be one of a number of tools local officials may use to reduce alcohol‐related crime in specific areas of a city, especially less‐serious crimes. In contrast to previous studies (Barajas et al, 2011; Collins et al, 2007; Jones‐Webb, et al, 2018; McKee et al, 2017; Vilamovska et al, 2009), our results also suggest that restrictions of malt liquor sales in AIAs may also be helpful in reducing more‐serious alcohol‐related crime, such as aggravated assault. Indeed, assaults (aggravated + simple) decreased in all 3 AIAs following mandatory restrictions on malt liquor sales.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings suggest that AIAs may be one of a number of tools local officials may use to reduce alcohol‐related crime in specific areas of a city, especially less‐serious crimes. In contrast to previous studies (Barajas et al, 2011; Collins et al, 2007; Jones‐Webb, et al, 2018; McKee et al, 2017; Vilamovska et al, 2009), our results also suggest that restrictions of malt liquor sales in AIAs may also be helpful in reducing more‐serious alcohol‐related crime, such as aggravated assault. Indeed, assaults (aggravated + simple) decreased in all 3 AIAs following mandatory restrictions on malt liquor sales.…”
Section: Discussioncontrasting
confidence: 99%
“…AIAs in Washington were designed to reduce alcohol problems related to chronic public inebriation, and public inebriation is typically associated with street or less-serious crimes, such as panhandling, public urination, litter, and broken glass. Previous studies have also shown that malt liquor restrictions were associated with decreases in less-serious crime (Barajas et al, 2011;Calvert et al, 2020;Collins et al, 2007;Jones-Webb et al, 2018;McKee et al, 2017;Vilamovska et al, 2009). In contrast to these studies, our study found that AIAs were associated with decreases in more-serious Part I crime as well in the Tacoma AIA.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations